Ecotoxicity and recovery of Poecilia reticulata exposed to cosmetic effluent, graphene oxide, iron oxide nanoparticles and magnetic graphene oxide - Walter de Souza Rodrigues; João Marcos de Lima Faria; Diego Stéfani Teodoro Martinez; Theodoro da Rosa Salles; Victoria Costa da Silva; Débora dos Santos Pereira; Ryan Marques Rezende; Ana Luiza Torres Soares; Isabela Cristina Louza Goulart; Jordana Duarte de Souza; Lucas Camilo Moraes Alves; Simone Maria Teixeira de Sabóia-Morais (Aquatic Toxicology, 2026)

Mitigation of pesticide residues in rice: influence of cooking methods on long-grain, brown, and Basmati varieties - Filipa Carreiró; Sílvia Cruz Barros; Carla Brites; Patrícia Cazón; Duarte Torres; Fernando Ramos; Ana Sanches Silva (Food Additives & Contaminants: Part A, 2026)

Potato protein-based meat analogues fortified with upcycled fruit flours: Functional, textural, and antioxidant insights - Ana Rita Pereira; Vasco Trincão da Silva; Duarte Torres; Ana A. Vilas-Boas; Débora A. Campos; Inês Cruz; Adriana Ferreira; Nuno Mateus; Victor de Freitas; Ana Fernandes (Food Chemistry, 2026)

Associations between food contaminants exposure and pubertal development at 10 and 13 years old - Sofia Almeida Costa; Milton Severo; Catarina Campos Silva; Carla Lopes; Duarte Torres (Environmental Research, 2026)

Genetic evaluation of growth and reproductive traits in Nelore cattle under humid tropical conditions - Elizangela Zayana Lima D´suze; Jhonathan Carvalho Senger; Eula Regina Carrara; Nilsa Duarte da Silva Lima; Jalison Lopes; Henrique Torres Ventura; José Teodoro de Paiva (Tropical Animal Health and Production, 2026)
Assessing the genetic variability of economically important traits is key to guiding selection strategies, and monitoring its changes over time provides critical support for decision-making. The study aimed to estimate genetic parameters and evaluate genetic and phenotypic trends for growth and reproductive traits in Nelore cattle raised under humid tropical conditions. Growth traits included weaning weight ( n = 1266), yearling weight ( n = 832), and post-yearling weight ( n = 733); while reproductive traits included age at first calving ( n = 639), calving interval ( n = 1772), and stayability ( n = 1122), recorded from 2016 to 2022. Variance components were estimated using Bayesian inference, and temporal trends were assessed through linear regression of phenotypic and genetic values on birth year. Growth traits showed moderate to high heritability (ranging from 0.43 to 0.58), indicating good potential for response to selection. Reproductive traits exhibited low heritability (0.04–0.13), reflecting greater environmental influence. Favorable phenotypic trends were observed for weaning weight (3.09 kg/year), yearling weight (2.72 kg/year), post-yearling weight (3.91 kg/year), age at first calving (− 0.68 months/year), and calving interval (− 11.90 days/year). Genetic progress was observed for age at first calving (− 0.03 months/year) and calving interval (− 3.35 days/year), while the remaining traits showed no significant changes. These findings support the use of growth traits for genetic improvement while reinforcing the importance of integrating selection with management strategies to enhance reproductive performance of Nelore cattle under humid tropical conditions.

In situ activation of RuO2 nanocrystals supported on NbOPO4 for solvent-free transalkylation and hydrodeoxygenation of eucalyptus bio-oil - Yuri Gontijo Rosa; Victor Muniz Soares; Samuel Moura Breder; Francyellen Cota Torres; Luiz Carlos Alves Oliveira; Henrique Oliveira; Vânya Márcia Duarte Pasa (Chemical Engineering Journal, 2026)

Effects of exposure to lisdexamfetamine dimesylate on hepatic parameters of pubertal rats - João Vinícius Honório da Silva; Letícia Cavalcante Santos; Rafaela Pires Erthal; Dayane Priscila dos Santos; Camila Rodrigues Ferraz; Camila Franciele de Souza; Luís Eduardo Duarte Gonçalves; Waldiceu Aparecido Verri; Niels Olsen Saraiva Câmara; Ernane Torres Uchôa; Glaura Scantamburlo Alves Fernandes; Fábio Goulart de Andrade (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Acrylamide daily dietary exposure and cardiometabolic outcomes: longitudinal approach from childhood to adolescence - Sofia Almeida Costa; Milton Severo; Carla Lopes; Duarte Torres (Food Additives & Contaminants: Part A, 2026)

Marine litter is a notable challenge to crabs in highly impacted mangrove areas: a case study in Guanabara Bay, SE Brazil - Eduardo Vianna de Almeida; Priscilla de Oliveira Gomes dos Santos; Luciana Pereira Torres Chequer; Viviane Duarte Gonçalves; Tainá Stauffer; Jorge Elias Rage-Aboud; Carla Muniz Sabino; Gabriela Verônica Buraschi; Susana Beatriz Vinzon (Environmental Monitoring and Assessment, 2026)
Mangroves represent a particularly vulnerable coastal ecosystem to the problem of marine litter. However, research addressing the impact of macroscopic litter on mangrove crabs remains limited. The aim of this study was to characterize diversity, abundance, and size of the semi-terrestrial crabs in a mangrove swamp heavily affected by macroscopic marine litter, in Southeastern Brazil. It was also aimed at verifying any potential correlations between crab parameters and the percentage of substrate covered by marine litter. Quadrats of 3.0 m × 3.0 m were used in three subzones of the intertidal zone (lower, middle, and transition—between upper intertidal and supralittoral). The litter was characterized after collection, and marine litter coverage was assessed using 1.0 m × 1.0 m photographs, which were analyzed using CPCe software. The fiddler crabs were analyzed by catch and release and the crab Ucides cordatus by examination and counting of burrows. The abundance of marine litter ranged from 69.6 to 120.3 items.m −2 , and the marine litter coverage varied between 26.0 and 100.0%. The diversity and abundance of crab species was found to be low (0.32 to 1.46 bits; 0.1 to 2.0 ind.m −2 ). The marine litter coverage had a significant negative effect on crab abundance ( R = −0.63; p = 0.03). In addition, a strong and significant influence of marine litter coverage on the size of both U. cordatus (Pearson, R = 0.83; p = 0.02) and Minuca spp. (only females; Pearson, R = 0.80; p < 0.001) was observed.

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

Synthetic cannabidiol analogues exhibit lower toxicity than cannabidiol and protect against ethanol-induced apoptosis in SH-SY5Y cells - Carolina Aparecida Faria Almeida; Gabriela Salles; Vitor Bruno; Jessyca Milene Ribeiro; Alessandra Oliveira Silva; Giulia de Assis Braz; Felype Valentim Duarte Castelhano; Graziella dos Reis Rosa Franco; Cláudio Viegas; Tania Marcourakis; Larissa Helena Lobo Torres; Raphael Caio Tamborelli Garcia (NeuroToxicology, 2026)

Fumonisins’ risk assessment in broa, a maize-based bread – An example from the Portuguese market - Pedro Nabais; Paulo Carmona; Sarogini Monteiro; Helena Sousa; Filipa Melo de Vasconcelos; Duarte Torres; Laura Cunha Silva (Food Control, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Effect of Heterorhabditis bacteriophora (HB EN01) and Steinernema rarum (PAM 25) nematodes on the control of cattle tick Rhipicephalus (Boophilus) microplus (Acari: Ixodidae) - E.R. Souza; J.G.C. Orozco; F.C. Duarte; L.C. Torres; M.C. Mendes (Veterinary Parasitology, 2025)

Dietary exposure to heterocyclic amines by the Portuguese population: comparison of different exposure assessment methods - Marta Pinto da Costa; Daniela Correia; Catarina Carvalho; Sofia Vilela; Vânia Magalhães; Milton Severo; Carla Lopes; Duarte Torres (Food and Chemical Toxicology, 2025)

Ontogenic, Immunological, and Behavioral Changes of Crack Cocaine Exposure During the Gestational Period - Yngrid Mickaelli Oliveira dos Santos; Igor Santana-Melo; Amanda Larissa Dias Pacheco; Milenna Maria Jatoba Hasten Reiter; Maisa de Araújo Costa; Keyla Silva Nobre Pires; Fernanda Maria Araújo de Souza; Jucilene Freitas-Santos; Mayara Rodrigues Barbosa; Jeferson Santana Ursulino; Marvin Paulo Lins; Rayssa Gabriely Duarte Torres; et al. (Molecular Neurobiology, 2025)

Root-Stem Transition Zone Anatomy Assessment in Hormonal Variants of Tomato, After Growing Under Contrasting Water Saturation - Rodrigo Barbosa Kloss; Felipe Della Torre; Vinícius Politi Duarte; Fabricio José Pereira; Joni Esrom Lima; Marcel Giovanni Costa França (Journal of Plant Growth Regulation, 2025)

Ketamine-Ethanol Combination Decreases Reduced Glutathione Levels and Activates both Intrinsic and Extrinsic Apoptotic Pathways Prior to Neuronal Death in SH-SY5Y Cells - Felype Valentim Duarte Castelhano; Carolina Aparecida de Faria Almeida; Giulia de Assis Braz; Gabriela Otofuji Pereira; Rafaela Yolanda Silvino de Almeida; Matheus Lujan Pereira; Juliana Ligia Freires Ribeiro; Karin Argenti Simon; Rodrigo Portes Ureshino; Tania Marcourakis; Larissa Helena Torres; Raphael Caio Tamborelli Garcia (Neurotoxicity Research, 2025)

Management intensity does not affect the ecological indicators of coffee agroforestry systems in agricultural landscapes of the Atlantic forest zone in Brazil - Vitoria Duarte Derisso; Ricardo Gomes César; Catherine Torres de Almeida; Pedro H. S. Brancalion; Danilo R. A. Almeida; Paulo G. Molin; Aline Souza; Edson Vidal (Agroforestry Systems, 2025)

Corrigendum to ‘Pressure drop prediction for R407C fluid during flow evaporation in horizontal pipes using Kalman filter’ [International Journal of Refrigeration 168 (2024) 149–158] - Gabriel Gonçalves Lemes de Souza; Willian Moreira Duarte; Raphael Nunes de Oliveira; Antônio Augusto Torres Maia (International Journal of Refrigeration, 2025)

Pressure drop prediction for R407C fluid during flow evaporation in horizontal pipes using Kalman Filter - Gabriel Gonçalves Lemes de Souza; Willian Moreira Duarte; Raphael Nunes de Oliveira; Antônio Augusto Torres Maia (International Journal of Refrigeration, 2024)

Accumulation of podophyllotoxin in the root culture of Hyptis suaveolens (L.) Poit: A potential natural lignan for clinically useful anticancer drugs - Sâmia Torres Silva; Rafael Marlon Alves de Assis; Adriane Duarte Coelho; Simony Carvalho Mendonça; Lurdeslaine Faria Texeira; Suzan Kelly Vilela Bertolucci; José Eduardo Brasil Pereira Pinto (Biocatalysis and Agricultural Biotechnology, 2024)

Exploring dietary patterns and their association with environmental sustainability and body mass index in children and adolescents: Insights from the National Food, Nutrition and Physical Activity Survey 2015–2016 - Beatriz Teixeira; Cláudia Afonso; Milton Severo; Catarina Carvalho; Duarte Torres; Carla Lopes; Andreia Oliveira (Science of The Total Environment, 2024)

Association between bisphenol A exposure and cardiometabolic outcomes: A longitudinal approach - Sofia Almeida Costa; Milton Severo; Carla Lopes; Duarte Torres (Journal of Hazardous Materials, 2024)

Protection of cowpea seeds and toxicity against cowpea weevils by the essential oils from Lippia alba (verbenaceae) and Schinus terebinthifolius (anacardiaceae) - Rafael Torre; Elisabeth Alves Duarte Pereira de Medeiros; Camila da Silva Barbosa Pereira; Ana Clara Ramos Menezes; Igor Sampaio Fontes; Larissa Vitória Ribeiro Pereira; Diego Henrique Fernandes Paiva; André Marques dos Santos; Pedro Corrêa Damasceno Junior; Marco Andre Alves de Souza (Crop Protection, 2024)

Do invasive and native grasses in Brazilian Savanna differ in their photosynthetic performance under natural light radiation? - Áurea Rodrigues Cordeiro; Alexandre Aparecido Duarte; Felipe Della-Torre; Fernando Afonso Nonato França; Marcel Giovanni Costa França (Flora, 2024)

Anaerobic co-digestion of microalgal biomass, sugarcane vinasse, and residual glycerol from biodiesel using simplex-centroid mixture design: methane potential, synergic effect, and microbial diversity - Edilberto Mariano da Silva; Sayonara Costa de Araújo; Shyrlane Torres Soares Veras; Agnes Adam Duarte Pinheiro; Fabrício Motteran; Mario Takayuki Kato; Lourdinha Florencio; Wanderli Rogério Moreira Leite (Environmental Science and Pollution Research, 2024)

Dog in sheep’s clothing: livestock depredation by free-ranging dogs may pose new challenges to wolf conservation - Sofia Lino; Mariana Rossa; Joana M. Fernandes; Tânia Barros; Ana Lino; Dário Hipólito; Eduardo Ferreira; Sara C. Aliácar; Duarte Cadete; Carlos Fonseca; Rita T. Torres; Luís M. Rosalino; et al. (European Journal of Wildlife Research, 2023)
Livestock depredation is a common cause of human-carnivore conflicts. In Portugal, free-ranging dogs are increasingly abundant and overlap endangered Iberian wolf territories, with reports of livestock depredation. However, the lack of awareness about dogs’ possible role as predators leads to bias against wolves in cases of damages. Our goal was to assess and compare wolf and free-ranging dog’s diet composition at southern wolf range in Portugal, to offer insights on dogs’ predatory role on livestock and its implications for the conservation of an endangered wolf subpopulation. We assessed diet composition from 107 to 95 genetically confirmed wolf and dog scats, respectively, and complemented the analysis with data from 40 attacks on livestock with successful genetic predator assignment. Scat analysis highlighted goats as the most consumed dog prey in all analysed regions, with lagomorphs, small mammals, and wild boars as second most consumed in each region, respectively. Wolves mainly relied on goats and wild boars in the west, whereas in the central region they mostly fed on birds. The dietary overlap between both canids was very high (Pianka’s index O = 0.93), showing potential for competition. Additionally, we found that dogs were the sole predators detected in most attacks (62%). Our findings highlight dogs’ role as predators of livestock, and possibly also wild species, posing a further challenge to wolf conservation. Alongside adequate husbandry practices, we emphasise the need for a stronger enforcement of the legislation on dog ownership and an effective management of the stray population to reduce human-wolf conflict.

Methodological approaches for the assessment of bisphenol A exposure - Sofia Almeida Costa; Milton Severo; Daniela Correia; Catarina Carvalho; Vânia Magalhães; Sofia Vilela; Sara Cunha; Susana Casal; Carla Lopes; Duarte Torres (Food Research International, 2023)

Assessing the environmental impact of diet – Influence of using different databases of foods' environmental footprints - Catarina Carvalho; Daniela Correia; Sofia Almeida Costa; Carla Lopes; Duarte Torres (Journal of Cleaner Production, 2023)

Screening of medicinal plants from El Salvador for anti-viral activity against Herpes simplex 1 - José Franco-Espínola; Marvin J. Núñez; Y. Mabel Sanabria-Ramírez; Carlos Fabio Villar-Duarte; Ulises G. Castillo; Guadalupe Cantero-González; Marcos Florentín-Pavía; Patricia Langjahr; Pablo Hernán Sotelo Torres (Natural Product Research, 2023)

Melatonin improves behavioral parameters and oxidative stress in zebrafish submitted to a leucine-induced MSUD protocol - Mariane Bernardo Duarte; Bianca Zampiroli Medeiros; Isabela da Silva Lemos; Guilherme Lodetti da Silva; Carolina Giassi Alano; Eduardo Ronconi Dondossola; Carolina Antunes Torres; Pauline Souza Effting; Eduardo Pacheco Rico; Emilio Luiz Streck (Metabolic Brain Disease, 2023)

Inferring the territoriality of Upper Palaeolithic hunter-gatherer’s groups settled at Cueva del Gato 2 (Épila, Zaragoza) - Marta Sánchez de la Torre; Luis Jiménez Ruiz; Bernard Gratuze; Elsa Duarte; María Fernanda Blasco; José María Rodanés (Archaeological and Anthropological Sciences, 2023)
In recent decades, the development of different analytical procedures applied to the study of archaeological lithic remains has allowed us to approach the territoriality of past societies. The application of geochemical tools has improved the study of lithic raw materials, allowing direct connections between archaeological samples and specific geological formations. In a similar way, the incorporation of GIS tools to the study of past mobility and territoriality has allowed to define which could have been the most probable routes used by past groups to stock up on rocks. In this paper, we present the results obtained after the geochemical study by Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS) of lithic cherts found at Upper Palaeolithic human occupations at Cueva del Gato 2 (Épila, Zaragoza, Spain) as well as the least cost path routes obtained after GIS analyses. The Cueva del Gato 2 archaeological site is a large cave placed in the first foothills of the Iberian System, close to the Middle Ebro Basin, in Eastern Iberia. The archaeological work has revealed a long sequence of occupation with archaeological levels from the Bronze Age, the Ancient Neolithic and the Upper Palaeolithic. In this paper, we have focused on the study of level II, which has been dated in the range 21,000–23,000 cal BP. Results have demonstrated that past human groups from the Last Glacial Maximum knew and frequented the Sierra de Lanaja – Montes de Castejón lacustrine chert sources, outcropping in the Middle Ebro Basin.

Anthocyanin bioaccessibility and anti-inflammatory activity of a grape-based 3D printed food for dysphagia - Alan Giovanini de Oliveira Sartori; Ana Sofia Martelli Chaib Saliba; Bruna Sousa Bitencourt; Jaqueline Souza Guedes; Larissa Catelli Rocha Torres; Severino Matias de Alencar; Pedro Esteves Duarte Augusto (Innovative Food Science & Emerging Technologies, 2023)

Maternal dietary exposure to mycotoxin aflatoxin B1 promotes intestinal immune alterations and microbiota modifications increasing infection susceptibility in mouse offspring - Patricia Bastos-Amador; Elsa Leclerc Duarte; Júlio Torres; Ana Teresa Caldeira; Inês Silva; Cátia Salvador; Ricardo Assunção; Paula Alvito; Manuela Ferreira (Food and Chemical Toxicology, 2023)

Combined effects of climate change stressors and predators with contrasting feeding-digestion strategies on a mussel species - Patricio H. Manríquez; Claudio P. González; María Elisa Jara; Sue-Ann Watson; Rodrigo Torres; Paolo Domenici; Cristian Duarte (Marine Pollution Bulletin, 2023)

Exposure to leucine alters glutamate levels and leads to memory and social impairment in zebrafish - Isabela da Silva Lemos; Leticia Burato Wessler; Mariane Bernardo Duarte; Guilherme Lodetti da Silva; Henrique Teza Bernardo; Gabriela Candiotto; Carolina Antunes Torres; Fabricia Petronilho; Eduardo Pacheco Rico; Emilio Luiz Streck (Metabolic Brain Disease, 2022)

Dietary exposure to artificial sweeteners and associated factors in the Portuguese population - Catarina Carvalho; Daniela Correia; Milton Severo; Vânia Magalhães; Susana Casal; Elisabete Ramos; Carla Lopes; Duarte Torres (Food Additives & Contaminants: Part A, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Risk characterization of dietary acrylamide exposure and associated factors in the Portuguese population - Sofia Almeida Costa; Daniela Correia; Catarina Carvalho; Sofia Vilela; Milton Severo; Carla Lopes; Duarte Torres (Food Additives & Contaminants: Part A, 2022)

Exposure to leucine induces oxidative stress in the brain of zebrafish - Bianca Z. de Medeiros; Leticia B. Wessler; Mariane B. Duarte; Isabela S. Lemos; Gabriela Candiotto; Rafael O. Canarim; Paulo C. L. dos Santos; Carolina A. Torres; Giselli Scaini; Eduardo P. Rico; Jaqueline S. Generoso; Emilio L. Streck (Metabolic Brain Disease, 2022)

Microclimate and animal thermal comfort indexes in different silvopastoral system arrangements in Caatinga - Clemente Fernandes dos Santos Neto; Rodrigo Gregório da Silva; Samuel Rocha Maranhão; Antônia Flávia Fernandes Torres; José Antonio Delfino Barbosa Filho; Vitor Hugo Maués Macedo; Magno José Duarte Cândido (International Journal of Biometeorology, 2022)

Biological activities of the essential oil from the leaves of Lantana montevidensis (Spreng) Briq. in mice - Maria Rayane Correia de Oliveira; Maria Gabriely de Lima Silva; Isabel Sousa Alcântara; Jaime Ribeiro Filho; Cícera Datiane de Morais Oliveira Tintino; Francisco Ernani Alves Magalhães; Anita Oliveira Brito Pereira Bezerr Martins; Renata Torres Pessoa; Antonia Eliene Duarte; José Galberto Martins da Costa; Sidney Gonçalo de Lima; Henrique Douglas Melo Coutinho; et al. (Environment, Development and Sustainability, 2021)

Administration of branched-chain amino acids alters epigenetic regulatory enzymes in an animal model of Maple Syrup Urine Disease - Emilio L. Streck; Felipe P. Bussular; Leticia B. Wessler; Mariane B. Duarte; Victoria L. Rezende; Matheus S. Rodrigues; Carolina A. Torres; Isabela S. Lemos; Gabriela Candiotto; Fernanda F. Gava; Jade de Oliveira; Samira S. Valvassori (Metabolic Brain Disease, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Evaluation of natural regeneration and recovery of environmental services in a watershed in the Cerrado-Brazil - Gilsonley Lopes dos Santos; Marcos Gervasio Pereira; Rafael Coll Delgado; José Luiz Rodrigues Torres; Matheus Duarte da Silva Cravo; Antônio Carlos Barreto; Iris Cristiane Magistrali (Environment, Development and Sustainability, 2020)

Food insecurity and social determinants of health among immigrants and natives in Portugal - Violeta Alarcão; Sofia Guiomar; Andreia Oliveira; Milton Severo; Daniela Correia; Duarte Torres; Carla Lopes (Food Security, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Expression of DREB-Like Genes in Coffea canephora and C. arabica Subjected to Various Types of Abiotic Stress - Luana Ferreira Torres; Tharyn Reichel; Eveline Déchamp; Sinara Oliveira de Aquino; Karoline Estefani Duarte; Gabriel Sergio Costa Alves; Anderson Tadeu Silva; Michelle Guitton Cotta; Tatiana Santos Costa; Leandro Eugenio Cardamone Diniz; Jean-Christophe Breitler; Myriam Collin; et al. (Tropical Plant Biology, 2019)

Relationship between the environmental conditions and floristic patterns in two phytophysiognomies of the Brazilian Cerrado - Gilsonley Lopes dos Santos; Marcos Gervasio Pereira; Daniel Costa de Carvalho; Raíssa Nascimento dos Santos; Rafael Coll Delgado; José Luiz Rodrigues Torres; Matheus Duarte da Silva Cravo (Environment, Development and Sustainability, 2019)

Distribution of CR1-like transposable element in woodpeckers (Aves Piciformes): Z sex chromosomes can act as a refuge for transposable elements - Natasha Avila Bertocchi; Thays Duarte de Oliveira; Analía del Valle Garnero; Rafael Luiz Buogo Coan; Ricardo José Gunski; Cesar Martins; Fabiano Pimentel Torres (Chromosome Research, 2018)

Prevalence of naturally occurring amino acid substitutions associated with resistance to hepatitis C virus NS3/NS4A protease inhibitors in São Paulo state - Regina Célia Moreira; Ana Paula de Torres Santos; Gaspar Lisboa-Neto; Maria Cássia Jacintho Mendes-Corrêa; Marcilio Figueiredo Lemos; Fernanda Mello Malta; Rúbia Anita Ferraz Santana; Gregório Tadeu Fernando Dastoli; Vanessa Fusco Duarte de Castro; João Renato Rebello Pinho (Archives of Virology, 2018)

Evaluation of Learning in Oncology of Undergraduate Nursing with the Use of Concept Mapping - Mariane Trevisani; Cibelli Rizzo Cohrs; Mariângela Abate de Lara Soares; José Marcio Duarte; Felipe Mancini; Ivan Torres Pisa; Edvane Birelo Lopes De Domenico (Journal of Cancer Education, 2016)

Ocean acidification induces changes in algal palatability and herbivore feeding behavior and performance - Cristian Duarte; Jorge López; Samanta Benítez; Patricio H. Manríquez; Jorge M. Navarro; Cesar C. Bonta; Rodrigo Torres; Pedro Quijón (Oecologia, 2016)

Analysis of volatile components from Melipona beecheii geopropolis from Southeast Mexico by headspace solid-phase microextraction - Ahira Torres-González; Paulina López-Rivera; Georgina Duarte-Lisci; Ángel López-Ramírez; Adriana Correa-Benítez; J. Fausto Rivero-Cruz (Natural Product Research, 2016)

CO2-Driven Ocean Acidification Disrupts the Filter Feeding Behavior in Chilean Gastropod and Bivalve Species from Different Geographic Localities - Cristian A. Vargas; Victor M. Aguilera; Valeska San Martín; Patricio H. Manríquez; Jorge M. Navarro; Cristian Duarte; Rodrigo Torres; Marco A. Lardies; Nelson A. Lagos (Estuaries and Coasts, 2015)

Functional repetitive sequences and fragile sites in chromosomes of Lolium perenne L. - Laiane Corsini Rocha; Fernanda de Oliveira Bustamante; Raphaela Aparecida Duarte Silveira; Giovana Augusta Torres; Andréa Mittelmann; Vânia Helena Techio (Protoplasma, 2015)

Intraspecific Variability in the Response of the Edible Mussel Mytilus chilensis (Hupe) to Ocean Acidification - Cristian Duarte; Jorge M. Navarro; Karin Acuña; Rodrigo Torres; Patricio H. Manríquez; Marcos A. Lardies; Cristian A. Vargas; Nelson A. Lagos; Víctor Aguilera (Estuaries and Coasts, 2015)

Habitat monitoring and genotoxicity in Ucides cordatus (Crustacea: Ucididae), as tools to manage a mangrove reserve in southeastern Brazil - M. A. A. Pinheiro; L. F. A. Duarte; T. R. Toledo; M. L. Adam; R. A. Torres (Environmental Monitoring and Assessment, 2013)

Host selection and establishment of striped mealybug, Ferrisia virgata, on cotton cultivars - Christian Sherley Araújo da Silva-Torres; Martin Duarte de Oliveira; Jorge Braz Torres (Phytoparasitica, 2013)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effects of melatonin on orofacial movements in rats - Abílio V.; Vera J.; Ferreira L.; Duarte C.; Carvalho R.; Grassl C.; Martins C.; Torres-Leite D.; Bignotto M.; Tufik S.; de Ribeiro; Frussa-Filho R. (Psychopharmacology, 2002)